The impact of organizational ethics to the project performance - Norhasimah , A Rahman (2014)
This research aim is to determine the impact of organizational ethics to the project performance and the relationship between these two variables from the perspective of contractors. This research helps the organization to improve their ethics in order to run the project and to have good value. This research has provided a greater understanding of project performance and the importance of ethics in organization. The way of this research being conducted is by using the non-probability sampling with the number of samples of 52 respondents. Then, the quantitative approach is used as a research method. Next, to run the data, the Statistical Package for Social Science (SPSS) has been performed. For example, the demographic, correlation analysis, regression analysis and descriptive analysis. Based on the analysis, the dimension of organizational ethics such as absenteeism, cyberloafing and lateness of coming to work has a moderate positive relationship with the project performance. Besides that, using the descriptive analysis, it shows that, the lateness of coming to work has the highest dispersion compared to the other two dimensions